2009
DOI: 10.1071/wr08165
|View full text |Cite
|
Sign up to set email alerts
|

Shedding new light on old species identifications: morphological and genetic evidence suggest a need for conservation status review of the critically endangered bat, Saccolaimus saccolaimus

Abstract: Information based on the accurate identification of species is a vital component for achieving successful outcomes of biodiversity conservation and management. It is difficult to manage species that are poorly known or that are misidentified with other similar species. This is particularly problematic for rare and threatened species. Species that are listed under endangered species classification schemes need to be identified accurately and categorised correctly so that conservation efforts are appropriately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Accurate classification is thus an essential first step towards effective conservation of local biodiversity [2][3]. This is particularly critical in the Southern Hemisphere, where a high proportion of endemic species are poorly known, and are now threatened by non-native introductions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate classification is thus an essential first step towards effective conservation of local biodiversity [2][3]. This is particularly critical in the Southern Hemisphere, where a high proportion of endemic species are poorly known, and are now threatened by non-native introductions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Radius, D S. flaviventris formed two discrete clusters in terms of spectral parameters. Subsequent study revealed that one of these clusters resembled S. saccolaimus sequences from the Northern Territory, illustrated in Milne et al (2009). Fortuitously, the echolocation sequence emitted by one of the vouchered S. saccolaimus specimens was being recorded when it was shot (flying through the beam of a spotlight), thus providing a reference sequence from the Kimberley.…”
Section: Site (Figure 1) Wam# Sex Location (Wmg)mentioning
confidence: 97%
“…Consequently, we have reassigned Kimberley sequences to S. saccolaimus if they match, or are in continuous sequence with pulse-series that match, (1) the Kimberley reference sequence (by specimen M49194, flying in open air above tree canopy) and/ or (2) the descriptors for sequence-types (b) and (c) in Fig. 4 of Milne et al (2009). Their study identified three different search mode sequences from Anabat-ZCAIM reference recordings of Northern Territory S. saccolaimus, each emitted in a different environmental setting.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations